Small intestine development of laying hens fed different fiber sources diets and crude protein levels - Praes, MFFM [UNESP]; Pereira, AA [UNESP]; Sgavioli, S [UNESP]; Duarte, KF [UNESP]; Alva, JCR [UNESP]; Domingues, CH de F [UNESP]; Puzzoti, MM [UNESP]; Junqueira, Otto Mack [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2011)
The objective of the presente study was to evaluate the effects on different dietary fiber sources and crude protein levels on the intestinal morphometry of commercial layers. Isa Brown® layers with 48 weeks of age were distributed in a completely randomized experimental design with a 3 x 2 + 1 factorial arrangement, resulting in seven treatments with seven replicates of eight birds each. At the end of the fourth experimental period (28 days each), birds were 64 weeks of age and were randomly chosen (two birds per replicate, totaling 14 birds per treatment), weighed and sacrificed by neck dislocation. Their intestine was dissected and the duodenum, jejunum and ileum were collected for subsequent analysis of intestinal morphometry. Treatments consisted of diets containing three different fiber sources (cottonseed hulls, soybean hulls or rice husks) and two crude protein levels (12% or 16%). Soybean hulls and 16% crude protein level promoted, in general, an increase in villus height and crypt depth in the three intestinal segments. In the duodenum, the control diet resulted in higher villus height and crypt depth relative to the diets containing fiber. In the jejunum, higher crypt depth values. In the ileum, dietary fiber increased villus height as compared to the control diet.
Keywords: Crude protein; fibers; intestinal development